Clinical significance of post‐prophylaxis cytomegalovirus infection in lung transplant recipients. Issue 4 (16th April 2018) - Jaamei, Nikta; Koutsokera, Angela; Pasquier, Jérôme; Mombelli, Matteo; Meylan, Pascal; Pascual, Manuel; Aubert, John‐David; Manuel, Oriol
Abstract: Cytomegalovirus (CMV) disease has been associated with the development of chronic lung allograft dysfunction (CLAD) after transplantation. However, the relevance of CMV replication occurring after the discontinuation of antiviral prophylaxis on the development of CLAD has not been fully established. Patients who underwent lung transplantation during 2004‐2014 were included. All patients received antiviral prophylaxis for 3‐6 months, followed by monitoring of CMV replication during the first year post‐transplantation (preemptive therapy). Risk factors for the development of CLAD were assessed by Cox models. A linear regression model with an interaction coefficient between time and CMV infection was used to evaluate the influence of CMV infection on the evolution of FEV1 . Overall, 69 patients were included, 30/69 (43%) patients developed at least 1 episode of significant CMV infection, and 8/69 (11.5%) patients developed CMV disease. After a median follow‐up of 3.67 years, 25/69 (36%) patients developed CLAD and 14/69 (20%) patients died. In the univariate Cox analysis, significant CMV infection (HR 1.177, P  = .698), CMV disease (HR 1.001, P  = .998), and duration of CMV replication (HR 1.004, P  = .758) were not associated with CLAD. Only bacterial pneumonia tended to be associated with CLAD in the multivariate model (HR 2.579, P  = .062). We did not observe a significant interaction between CMV replication and evolution FEV1 (interaction coefficient 0.006, CI 95% [−0.084 to 0.096], P  = .890). In this cohort of lung transplant recipients receiving antiviral prophylaxis and monitored by preemptive therapy post‐prophylaxis, CMV infection did not have impact on long‐term allograft lung function.